Sustainable leadership and its impact on organizational happiness Analytical research in the General Tourism Authority in Baghdad - Azafah, Raed Yusef; Mohammed, Nasreen Jassim (Journal of Economics and Administrative Sciences, 2021)
The current research aims to test the relationship of the impact of sustainable leadership as an independent variable in organizational happiness as a dependent variable, in the departments and divisions of the Tourism Authority, to come up with a set of recommendations that contribute to raising the level of organizational happiness in the authority. And based on the importance of the research topic in the General Authority, and the prominent role that this body plays in society, the researcher adopted the descriptive and analytical approach in carrying out this research, by collecting data from the departments and divisions staff of (160) respondents in an exclusively comprehensive manner, depending on the questionnaire. It contained (39) paragraphs, and with the help of field observations as tools to help in their collection. The researcher relied on the program (SPSS V.26, Smart PLS, Excel 2010) as well as the use of descriptive statistics methods (confirmatory factor analysis, percentages, arithmetic mean, standard deviation, coefficient of variation, simple linear regression, determination coefficient (R2), Analysis of the path, the relative importance, the Pearson correlation factor), while the most prominent conclusions reached by the researcher were that the Tourism Authority directs sustainable leadership practices positively in improving organizational happiness, through coherent diversity, employee development, orientation and progress, quality of work-life, as well as Organizational justice, in order, as well as the results of scientific research showed that the Tourism Authority has an interest in creating organizational happiness and enhancing it through its sustainable leadership. The research concluded with a number of recommendations that enhance the research variables in the Tourism Authority